Faktor – Faktor Yang Berhubungan Dengan Perkembangan Motorik Halus Anak Usia 4 Hingga 5 Tahun Di Paud Pelita Hati Kota Prabumulih Tahun 2024 - Nada Romadhona Yanuar; Bina Aquari; Sendy Pratiwi Rahmadhani; Erma Puspita Sari (STIKes Budi Mulia Sriwijaya, 2025)
Fine motor is a movement that uses fine muscles or a certain part of the body, the importance of optimizing fine motor makes children skilled in moving their fingers needed to learn to write, draw, pick up objects, and so on. The purpose of this study is to determine the relationship between nutritional status, stimulation and knowledge simultaneously with fine motor development in children aged 4 to 5 years at PAUD Pelita Hati Prabumulih in 2024. The research method is a quantitative method, the research design uses a cross sectional approach. The research was carried out in June-July 2024 at PAUD Pelita Hati, Prabumulih City. The population taken was all mothers who had children aged 4 to 5 years and children aged 4 to 5 years as many as 50 people, the sample taken was the entire population, the type of primary data, using a questionnaire instrument with interview techniques. Univariate analysis found that children's fine motor development was not suitable for 4 respondents (8%), children's fine motor development was according to 46 respondents (92%), malnutrition status of 4 respondents (8%) and normal nutritional status of 46 respondents (92%), poor stimulation of 5 respondents (10%) and good stimulation of 45 respondents (90%), poor knowledge of 6 respondents (12%) and good knowledge of 44 respondents (88%). The results of the bivariate analysis obtained a statistical test with a chi square test α = 0.005, there was a relationship between p-value nutritional status (0.028<0.05), there was a relationship between p-value stimulation (0.045<0.05) and there was a relationship between p-value knowledge (0.004<0.005) and fine motor development of children aged 4 to 5 years at PAUD Pelita Hati, Kota Prabumulih in 2024. The conclusion is that there is a relationship between nutritional status, stimulation and knowledge simultaneously with the fine motor development of children aged 4 to 5 years at PAUD Pelita Hati Kota Prabumulih in 2024. Can provide learning to parents and teachers on how to stimulate children according to age.